Treatment system hydraulics - Bergendahl, John (ASCE Press, 2008)
The success of a treatment system depends to a significant degree on the system's fluid flow, that is, on the selection and arrangement of pipes, channels, valves, pumps, and other hydraulic components that move fluid through the system. This book addresses the nuts-and-bolts of treatment systems, examining typical variables and describing methods for solving the problems faced by practitioners on a daily basis. The book begins with an introduction to treatment systems and hydraulics and explains the basic concepts of fluid properties, fluid statics, and fluid flow. The author discusses the factors that shape engineering decisions: friction in closed conduits, pumps and motors, granular media, valves, instrumentation, materials and corrosion, effects of transient conditions, and open channel flow. Each chapter presents fundamental concepts and applications in diverse situations, along with worked examples and problem sets. Suitable for undergraduate and graduate courses, the book is also a useful reference for environmental, mechanical, civil, and chemical engineers designing or managing water treatment facilities.
Keywords: Pipelines.; Hydraulic engineering.; Fluid dynamics.; Sewage disposal plants -- Design and construction.; Water treatment plants -- Design and construction.; Water -- Purification.; Sewage -- Purification.; elektronické knihy; electronic books